2016
DOI: 10.3390/ijms17060984
|View full text |Cite
|
Sign up to set email alerts
|

ROS and Brain Gliomas: An Overview of Potential and Innovative Therapeutic Strategies

Abstract: Reactive oxygen species (ROS) represent reactive products belonging to the partial reduction of oxygen. It has been reported that ROS are involved in different signaling pathways to control cellular stability. Under normal conditions, the correct function of redox systems leads to the prevention of cell oxidative damage. When ROS exceed the antioxidant defense system, cellular stress occurs. The cellular redox impairment is strictly related to tumorigenesis. Tumor cells, through the generation of hydrogen pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 111 publications
2
92
0
Order By: Relevance
“…Finally, elevated 2HG levels have been implicated in the production of high levels of ROS, possibly because of disruption of the NAPD/NAPDH balance during 2HG generation. Elevated ROS has been linked to mutagenesis and tumorigenesis …”
Section: Introductionmentioning
confidence: 99%
“…Finally, elevated 2HG levels have been implicated in the production of high levels of ROS, possibly because of disruption of the NAPD/NAPDH balance during 2HG generation. Elevated ROS has been linked to mutagenesis and tumorigenesis …”
Section: Introductionmentioning
confidence: 99%
“…So that, unlike the conclusions of other researchers [17,[64][65][66][67][71][72][73][74][75][76], I believe that the etiopathogenesis of low-grade gliomas is related with decreasing arterial blood flow (mild to severe ischemia) and by contrast, increasing and prolonged hypoxia (hypoxic microenvironment) associated with environmental carcinogens of endogenous and exogenous origin [12,14,41,54,62,77,78]. We currently know that there is a tendency toward a higher incidence of gliomas in highly industrialized countries, where they use ionizing radiation and are exposed to chemicals [78] and moreover, that the female sex hormones play a role in the development of gliomas in women [15].…”
Section: Genesis Of Gliomas In the Encephalonmentioning
confidence: 60%
“…Then, the immature glial cells originated from the SVZ, in its process of proliferation and migration to the cerebral cortex and gray nuclei [16,17,46,[64][65][66][67]79] and in a state of prolonged hypoxia [17,35,80], they emit different biochemical responses in order to minimize the progressive damage caused cytotoxic hypoxia. First, ROS generation by the mitochondrial electron transport chain, leading to activation of hypoxia-inducible factor-1 (HIF-1) and HIF-2 through PHD inhibition; [72,80] After surgery he received diphenylhydantoin and carbamazepine for one year. The epileptic seizures disappeared.…”
Section: Genesis Of Gliomas In the Encephalonmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that ROS participate in various pathways and can control cellular stability. 21 ROS may function as vital signaling molecules, which can favor tumorigenesis. [22][23][24] For example, restraining ROS in Listeria monocytogenes can promote glial cells apoptosis.…”
Section: Discussionmentioning
confidence: 99%